Satin glaze, antifouling wear-resistant satin glazed tile and preparation method thereof
Through careful selection and reasonable proportion of satin glazed tiles raw materials, combined with specific preparation steps, the surface defects of satin glazed tiles are solved, and products with high gloss, flatness and wear resistance are achieved.
Patent Information
- Application Number
- CN202411761570.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-04
AI Technical Summary
During the firing process, existing satin glazed tiles often have surface defects such as small bumps, pinholes, concave glaze, roller rod printing, etc., which affects the glaze texture and visual effect of the product.
By carefully selecting and reasonable proportioning of raw materials, controlling the silicon-aluminum ratio and barium content in the glaze, using additives such as barium strontium frit and zinc oxide, combined with specific ball milling and mixed pulping treatment steps, a satin glaze with excellent comprehensive performance is prepared.
The gloss is controlled at 10-15°, the surface flatness is maintained within ±0.2%, the wear resistance reaches 4 levels 2100 rpm, and the glaze has a silky touch.
Smart Images

Figure CN119551903A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic production technology, and specifically relates to a satin glaze, anti-fouling and wear-resistant satin glazed tile and a preparation method thereof. Background Art
[0002] With the development of social economy, people's requirements for home quality are increasing day by day, and high-quality decoration materials are becoming more and more popular among consumers. In recent years, a satin glazed tile product has appeared on the market. However, during the firing process of satin glaze products, surface defects such as small bumps (prickly heat bubbles), pinholes, concave glaze, roller marks, etc. often appear. These problems seriously affect the glaze texture and visual effect of the product. Therefore, the development of a satin glazed tile that is both anti-fouling and wear-resistant, has a good glaze effect and high flatness has become a technical challenge that needs to be solved urgently. Summary of the invention
[0003] In view of various surface defect problems existing in the existing satin glaze technology, the present invention provides a satin glaze, anti-fouling and wear-resistant satin glazed tile and a preparation method thereof. By carefully selecting and reasonably proportioning various raw materials, the silicon-aluminum ratio and the barium content in the glaze are controlled within an appropriate range, so that the prepared satin glaze has excellent comprehensive performance. When applied to ceramic tiles, the following effects can be achieved: glossiness is controlled at 10-15°, surface flatness is maintained within ±0.2%, wear resistance reaches level 4 2100 revolutions, and the glaze has a silky touch.
[0004] To solve the above problems, the present invention is implemented through the following technical solutions:
[0005] The first invention object of the present invention is:
[0006] Provided is a satin glaze comprising the following raw material components in percentage by weight:
[0007] Potassium feldspar powder 30-40%, talc powder 10-20%, kaolin 5-15%, zinc oxide 3-8%, barium carbonate 5-10%, dolomite 5-18%, calcite 2-5%, barium strontium frit 5-10%, quartz powder 0-2%, aluminum oxide 1-3%, the sum of all components is 100%;
[0008] The mass percentages of BaO and SrO in the barium strontium frit are 15-20% and 1-5% respectively.
[0009] Preferably, the barium strontium frit comprises the following raw material components in parts by weight:
[0010] 22 parts of quartz, 20 parts of non-calcined alumina, 32 parts of wollastonite, 4 parts of potassium feldspar, 1 part of sodium feldspar, 15-20 parts of barium carbonate, 1-5 parts of strontium carbonate, 2 parts of calcined talc, the sum of all the components is 100 parts.
[0011] The addition of barium strontium frit and zinc oxide can promote the precipitation of fine and soft crystals while enhancing the color of the glaze. The introduction of aluminum oxide can also improve the wear resistance of the glaze.
[0012] The further optimization of the satin glaze of the present invention is:
[0013] The mass percentage chemical composition of the satin glaze is:
[0014] SiO2 40~55%, Al2O3 10~15%, CaO 3~9%, MgO 3~9%, K2O+Na2O+Li2O3~8%, ZnO 3~8%, Ba0 5~15%, SrO 0.05~0.5%, Fe2O3+TiO2 0~0.8%, loss on ignition 8.5~12%, the sum of all components is 100%.
[0015] The second object of the present invention is:
[0016] A method for preparing the satin glaze as described above is provided, which comprises the following preparation steps:
[0017] a. Selecting corresponding raw materials according to the satin glaze formula, ball milling and mixing the selected raw materials to obtain a mixed satin glaze slurry;
[0018] The mixed satin glaze slurry has a 325-mesh sieve residue fineness of 0.1-0.2%, a specific gravity of 1.91-1.93, and a flow rate of 28-35 seconds;
[0019] b. The mixed satin glaze slurry obtained in step a is sequentially screened, iron removed, transferred to a slurry pool, screened for secondary iron removal, and aged and homogenized. After the treatment is completed, the satin glaze is prepared; or
[0020] The following steps are also included:
[0021] Before the ball milling and mixing slurry treatment in step a, 0.1-0.2 wt% of sodium carboxymethyl cellulose and 0.2-0.4 wt% of sodium tripolyphosphate and water are additionally added;
[0022] The weight ratio of the powder in the satin glaze raw material components to the additionally added water is 15:5 to 17:5.
[0023] The preparation method of the satin glaze of the present invention is further optimized as follows:
[0024] The screening and iron removal is completed by using a 160-mesh high-frequency circular vibrating screen in combination with an automatic iron remover.
[0025] The third invention object of the present invention is:
[0026] Provided is a stain-resistant and wear-resistant satin glazed tile, which comprises a surface glaze and the satin glaze described above.
[0027] The antifouling and wear-resistant satin glazed tile of the present invention is further optimized as follows:
[0028] The glaze comprises the following raw material components in percentage by weight:
[0029] Alumina 10-25%, feldspar powder 5-45%, talc powder 1-3%, kaolin 5-25%, nepheline powder 5-50%, quartz powder 5-15%, dolomite 1-3%, the sum of all components is 100%;
[0030] Add 5-10% zirconium silicate.
[0031] The antifouling and wear-resistant satin glazed tile of the present invention is further optimized as follows:
[0032] The mass percentage chemical composition of the glaze is:
[0033] SiO2 50~60%, Al2O3 25~35%, CaO+MgO 0.9~3.3, K2O+Na2O+Li2O 5~10%, ZrO0~10%, Fe2O3+TiO2 0~0.9%, loss on ignition 2.4~3.5%, the sum of all components is 100%.
[0034] The fourth invention objective of the present invention is:
[0035] Provided is a method for preparing the aforementioned anti-fouling and wear-resistant satin glazed tile, which comprises the following preparation steps:
[0036] S1. Applying the glaze on the body:
[0037] The glaze is applied twice by pouring, wherein the specific gravity of the top glaze is 1.87-1.92, the first glaze amount is (using a 34*67cm tray) 55±2g, and the second glaze amount is (using a 34*67cm tray) 60±2g;
[0038] S2. Inkjet printing of the design pattern on the body after the glaze is applied;
[0039] S3. Applying the satin glaze on the body after inkjet printing the design pattern to form a satin glaze layer:
[0040] The glaze is poured, the specific gravity of satin glaze is 1.87-1.92, the glaze amount is (using a 34*67cm tray) 110±2g, and the thickness does not exceed 3mm;
[0041] S4. sintering the green body after applying the satin glaze to prepare the satin glazed tile.
[0042] The preparation method of the anti-fouling and wear-resistant satin glazed tile of the present invention is further optimized as follows:
[0043] The glaze comprises the following preparation steps:
[0044] A. Selecting corresponding raw materials according to the glaze formula, ball milling and mixing the selected raw materials to obtain mixed glaze slurry;
[0045] The mixed glaze slurry has a 325-mesh sieve residue fineness of 0.1-0.2%, a specific gravity of 1.91-1.93, and a flow rate of 28-35 seconds;
[0046] B. the mixed glaze slurry obtained in step A is sequentially subjected to screening, iron removal, transfer to a slurry pool, secondary screening and iron removal, and aging and homogenization treatment, and after the treatment is completed, the glaze is prepared; or
[0047] The following steps are also included:
[0048] Before the ball milling and mixing slurry treatment in step A, 0.1-0.2 wt% of sodium carboxymethyl cellulose and 0.2-0.4 wt% of sodium tripolyphosphate and water are additionally added;
[0049] The weight ratio of the powder in the glaze raw material component to the additionally added water is 15:5 to 17:5.
[0050] The preparation method of the anti-fouling and wear-resistant satin glazed tile of the present invention is further optimized as follows:
[0051] The screening and iron removal is completed by using a 160-mesh high-frequency circular vibrating screen in combination with an automatic iron remover.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] First, the raw material formula is made into glaze raw materials; secondly, the glaze raw materials are ground and mixed to obtain a mixed slurry; then, the mixed slurry is successively subjected to iron removal, storage in a slurry tank and sieving for iron removal; then, the treated mixed slurry is subjected to glazing treatment, which is carried out twice during the process of applying the top glaze to promote the degassing of the blank and the glaze during the firing process and to fully react, so that the surface of the fired product is free of pinholes and bumps.
[0054] Secondly, the present invention adopts a satin glaze formula of a matte system composed of Ca, Mg, Ba, Zn, and Sr, reduces the use of high-temperature materials, improves the vitrification degree of the glaze, and thus has a strong anti-fouling ability. While ensuring the glossiness and anti-fouling ability, aluminum oxide is appropriately added to improve the wear resistance of the glaze. The glossiness of the prepared product is 10-15° measured by a gloss meter, the anti-fouling ability is good, the surface flatness is less than ±0.2%, the wear resistance reaches level 4 2100 revolutions, and the glaze has a silky touch. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 The present invention is a flow chart of the preparation process of the anti-fouling and wear-resistant satin glazed tile. DETAILED DESCRIPTION
[0056] In order to make the application, technical scheme and advantages of the present invention more clear, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the embodiments are only used to illustrate the present invention, but not to limit the protection scope of the present invention. All simple improvements to the preparation method of the present invention under the premise of the concept of the present invention belong to the protection scope of the present invention.
[0057] Example 1
[0058] A method for preparing anti-fouling and wear-resistant satin glazed tile, comprising the following preparation steps:
[0059] S1. Applying the glaze on the body:
[0060] The body temperature before glazing is 82±5℃;
[0061] The glaze is applied twice by pouring, wherein the specific gravity of the top glaze is 1.87-1.92, the first glaze amount is (using a 34*67cm tray) 55±2g, and the second glaze amount is (using a 34*67cm tray) 60±2g;
[0062] S2. Inkjet printing of the design pattern on the body after the glaze is applied;
[0063] S3. Applying the satin glaze on the body after inkjet printing the design pattern to form a satin glaze layer:
[0064] The body temperature before satin glaze is 60±5℃;
[0065] The glaze is poured, the specific gravity of satin glaze is 1.87-1.92, the glaze amount is (using a 34*67cm tray) 110±2g, and the thickness does not exceed 3mm;
[0066] S4. sintering the green body after applying the satin glaze to prepare the satin glazed tile.
[0067] The green body is fired as follows: the firing temperature of the roller kiln is 1160-1175° C. and the firing time is 32-36 minutes.
[0068] The glaze comprises the following preparation steps:
[0069] A. Selecting corresponding raw materials according to the glaze formula, ball milling and mixing the selected raw materials to obtain mixed glaze slurry;
[0070] Before the ball milling and mixing slurry treatment, 0.1-0.2 wt% of sodium carboxymethyl cellulose and 0.2-0.4 wt% of sodium tripolyphosphate and water are additionally added;
[0071] The weight ratio of the powder in the glaze raw material component to the additional water is 3:1;
[0072] The mixed glaze slurry has a 325-mesh sieve fineness of 0.1-0.2%, a specific gravity of 1.91-1.93, and a flow rate of 28-35 seconds;
[0073] B. the mixed glaze slurry obtained in step A is sequentially subjected to screening, iron removal, transfer to a slurry pool, secondary screening and iron removal, and aging and homogenization treatment, and after the treatment is completed, the glaze is prepared; or
[0074] The screening and iron removal is completed by using a 160-mesh high-frequency circular vibrating screen in combination with an automatic iron remover.
[0075] The satin glaze comprises the following raw material components in percentage by weight:
[0076] Potassium feldspar powder 35%, talc powder 15%, kaolin 10%, barium strontium frit 7.5%, barium carbonate 7.5%, dolomite 11.5%, calcite 3.5%, zinc oxide 5.5%, quartz powder 1.5%, aluminum oxide 3%;
[0077] The barium strontium frit comprises the following raw material components in parts by weight:
[0078] 20 parts of quartz, 18 parts of non-calcined alumina, 30 parts of wollastonite, 4 parts of potassium feldspar, 1 part of sodium feldspar, 20 parts of barium carbonate, 5 parts of strontium carbonate, and 2 parts of calcined talc.
[0079] The addition of the barium strontium frit and zinc oxide can not only promote the precipitation of fine and soft crystals, but also enhance the color of the glaze. At the same time, the introduction of aluminum oxide can also improve the wear resistance of the glaze.
[0080] The mass percentage chemical composition of the satin glaze is:
[0081] SiO2 43.19%, Al2O3 14.88%, CaO 7.49%, MgO 7.54%, K2O+Na2O+Li2O 4.92%, ZnO 5.46%, Ba0 6.17%, SrO 0.22%, Fe2O3+TiO2 0.29%, loss on ignition 9.84%.
[0082] The method for preparing the satin glaze comprises the following preparation steps:
[0083] a. Selecting corresponding raw materials according to the satin glaze formula, ball milling and mixing the selected raw materials to obtain a mixed satin glaze slurry;
[0084] Before the ball milling and mixing slurry treatment, 0.1-0.2 wt% of sodium carboxymethyl cellulose and 0.2-0.4 wt% of sodium tripolyphosphate and water are additionally added;
[0085] The ratio of the powder in the raw material components of the satin glaze to the additionally added water is in the range of 75:25 to 85:25;
[0086] The mixed satin glaze slurry has a 325-mesh sieve residue fineness of 0.1-0.2%, a specific gravity of 1.91-1.93, and a flow rate of 28-35 seconds;
[0087] b. The mixed satin glaze slurry obtained in step a is sequentially screened, iron removed, transferred to a slurry pool, screened for secondary iron removal, and aged and homogenized. After the treatment is completed, the satin glaze is prepared; or
[0088] The screening and iron removal is completed by using a 160-mesh high-frequency circular vibrating screen in combination with an automatic iron remover.
[0089] The glaze comprises the following raw material components in percentage by weight:
[0090] Alumina 17.5%, feldspar powder 25%, talc powder 2%, kaolin 15%, nepheline powder 27.5%, quartz powder 10%, dolomite 3%;
[0091] 7.5% zirconium silicate is added.
[0092] The mass percentage chemical composition of the glaze is:
[0093] SiO2 52.42%, Al2O3 31.22%, CaO+MgO 2.96, K2O+Na2O+Li2O 6.99%, ZrO3.25%, Fe2O3+TiO2 0.33%, loss on ignition 2.83.
[0094] Comparative Example 1
[0095] The preparation method of Comparative Example 1 is basically the same as that of Example 1, and the main difference is that only the method of applying the glaze is changed on the basis of Example 1, as follows:
[0096] Use one-time glazing with a specific gravity of 1.87-1.92 and a glazing amount (34*67cm tray) of 105±2g; then apply satin glaze according to the same steps and fire under the same conditions.
[0097] Comparative Example 2
[0098] The preparation method of Comparative Example 2 is basically the same as that of Example 1, and the main difference is that only the raw material composition of the satin glaze is changed on the basis of Example 1, as follows:
[0099] (1) Reduce the use of barium strontium frit to 4%
[0100] (2) Avoid the use of aluminum oxide, making the amount of aluminum oxide used 0
[0101] Then follow the same steps to glaze, ensure the glaze performance, control the weight and thickness, and fire under the same conditions.
[0102] The gloss comparison between the product prepared by the present invention and the comparative example, the product flatness and the decorative effect of the brick surface are shown in Table 1.
[0103] Table 1
[0104]
[0105]
[0106] The antifouling ability and wear resistance of the product prepared in Comparative Example 1 are basically consistent with those in Example 1, but the surface effect is poor, there are many small protrusions (prickly heat), and the glaze effect is poor.
[0107] The product prepared in Comparative Example 2 has poor antifouling ability and poor wear resistance.
[0108] To sum up, the above are only preferred embodiments of the present invention and are not intended to limit the present invention in any form. Any equivalent changes, modifications and evolutions made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
[0109] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0110] The experimental methods without specific conditions in the present invention are usually carried out under conventional conditions or conditions recommended by the manufacturer.
[0111] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.
[0112] Unless otherwise stated, percentages and parts are by mass.
[0113] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.
[0114] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.
Claims
1. A satin glaze, characterized in that: It includes the following raw material components in percentage by weight: Potassium feldspar powder 30-40%, talc powder 10-20%, kaolin 5-15%, zinc oxide 3-8%, barium carbonate 5-10%, dolomite 5-18%, calcite 2-5%, barium strontium frit 5-10%, quartz powder 0-2%, aluminum oxide 1-3%, the sum of all components is 100%; The mass percentages of BaO and SrO in the barium strontium frit are 15-20% and 1-5% respectively.
2. The satin glaze according to claim 1, characterized in that: The mass percentage chemical composition of the satin glaze is: SiO2 40~55%, Al2O3 10~15%, CaO 3~9%, MgO 3~9%, K2O+Na2O+Li2O3~8%, ZnO3~8%, Ba0 5~15%, SrO 0.05~0.5%, Fe2O3+TiO2 0~0.8%, loss on ignition 8.5~12%, the sum of all components is 100%.
3. A method for preparing the satin glaze according to claim 1, characterized in that: The satin glaze comprises the following preparation steps: a. Selecting the corresponding raw materials according to the satin glaze formula, ball-milling and mixing the selected raw materials to obtain a mixed satin glaze slurry; The mixed satin glaze slurry has a 325-mesh sieve residue fineness of 0.1-0.2%, a specific gravity of 1.91-1.93, and a flow rate of 28-35 seconds; b. The mixed satin glaze slurry obtained in step a is sequentially screened, iron removed, transferred to a slurry pool, screened for secondary iron removal, and aged and homogenized. After the treatment is completed, the satin glaze is prepared; or The following steps are also included: Before the ball milling and mixing slurry treatment in step a, 0.1-0.2 wt% of sodium carboxymethyl cellulose and 0.2-0.4 wt% of sodium tripolyphosphate and water are additionally added; The weight ratio of the powder in the satin glaze raw material components to the additionally added water is 15:5 to 17:
5.
4. The method for preparing satin glaze according to claim 3, characterized in that: The screening and iron removal is completed by using a 160-mesh high-frequency circular vibrating screen in combination with an automatic iron remover.
5. A stain-resistant and wear-resistant satin glazed tile, characterized in that: It comprises a top glaze and the satin glaze according to claim 1.
6. The anti-fouling and wear-resistant satin glazed tile according to claim 5, characterized in that: The glaze comprises the following raw material components in percentage by weight: Alumina 10-25%, feldspar powder 5-45%, talc powder 1-3%, kaolin 5-25%, nepheline powder 5-50%, quartz powder 5-15%, dolomite 1-3%, the sum of all components is 100%; Add 5-10% zirconium silicate.
7. The anti-fouling and wear-resistant satin glazed tile according to claim 5, characterized in that: The mass percentage chemical composition of the glaze is: SiO2 50~60%, Al2O3 25~35%, CaO+MgO 0.9~3.3, K2O+Na2O+Li2O 5~10%, ZrO 0~10%, Fe2O3+TiO2 0~0.9%, loss on ignition 2.4~3.5%, the sum of all components is 100%.
8. A method for preparing the anti-fouling and wear-resistant satin glazed tile according to claim 5, characterized in that: It comprises the following preparation steps: S1. Applying the glaze on the body: The glaze is applied twice by pouring, wherein the specific gravity of the top glaze is 1.87-1.92, the first glaze amount is 55±2g, and the second glaze amount is 60±2g; S2. Inkjet printing of the design pattern on the body after the glaze is applied; S3. Applying the satin glaze on the body after inkjet printing the design pattern to form a satin glaze layer: The glaze is poured, with a specific gravity of 1.87-1.92 for satin glaze, a glaze application amount of 110±2g, and a thickness of no more than 3mm. S4. sintering the green body after applying the satin glaze to prepare the satin glazed tile.
9. The method for preparing the antifouling and wear-resistant satin glazed tile according to claim 5, characterized in that: The glaze comprises the following preparation steps: A. Selecting corresponding raw materials according to the glaze formula, ball milling and mixing the selected raw materials to obtain mixed glaze slurry; The mixed glaze slurry has a 325-mesh sieve residue fineness of 0.1-0.2%, a specific gravity of 1.91-1.93, and a flow rate of 28-35 seconds; B. the mixed glaze slurry obtained in step A is sequentially subjected to screening, iron removal, transfer to a slurry pool, secondary screening and iron removal, and aging and homogenization treatment, and after the treatment is completed, the glaze is prepared; or The following steps are also included: Before the ball milling and mixing slurry treatment in step A, 0.1-0.2 wt% of sodium carboxymethyl cellulose and 0.2-0.4 wt% of sodium tripolyphosphate and water are additionally added; The weight ratio of the powder in the glaze raw material component to the additionally added water is 15:5 to 17:
5.
10. The method for preparing the anti-fouling and wear-resistant satin glazed tile according to claim 9, characterized in that: The screening and iron removal is completed by using a 160-mesh high-frequency circular vibrating screen in combination with an automatic iron remover.
Citation Information
Patent Citations
Satin glaze, satin glazed tile and preparation method of satin glazed tile
CN113912294A
Satin skin ceramic tile
CN115781892A
Micro-crystal micro-gloss glaze, micro-gloss ceramic rock plate with ultra-flat and fine glaze surface and preparation method of micro-crystal micro-gloss glaze and micro-gloss ceramic rock plate
CN115838245A
Digital low-light stone ceramic tile with skin texture as well as preparation method and application of digital low-light stone ceramic tile
CN116693330A
Preparation method of super-antifouling high-cleanliness satin glaze and ceramic tile thereof
CN117658468A